Glass cloth treatment liquid and surface-treated glass cloth
By using a glass cloth treatment solution containing a methacrylamide organic silicon compound, the problems of low stability and difficulty in improving the strength of the silane coupling agent in the prior art are solved, and efficient surface treatment and printing wiring of the glass cloth are achieved. The productivity of the substrate is improved.
Patent Information
- Application Number
- CN202380038982.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-09
- Filing Date
- 2023-04-28
- Publication Date
- 2025-01-10
AI Technical Summary
The silane coupling agent in the existing glass cloth treatment solution has low storage stability due to hydrolysis reaction and short application period. There are efficiency limitations when increasing the strength of the glass cloth, making it difficult to meet the productivity improvement needs of printed wiring substrates.
Using a glass cloth treatment solution containing a methacrylamide group, the silicone compound containing an organosilicon compound is adjusted to an acidic aqueous solution by dissolving 0.05 to 2.0 mass% of the compound in water, and the silicone compound containing a dimethacrylamide group is basically free of dimethacrylamide group. In order to treat glass cloth, ensure the stability and strength of the treatment liquid.
The storage stability and strength of the glass cloth are significantly improved, and are suitable for the manufacturing of printed wiring substrates, improving productivity and substrate reliability.
Smart Images

Figure CN119301322A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a glass cloth treating liquid and a surface-treated glass cloth, and more particularly to a glass cloth treating liquid containing an organosilicon compound containing a methacryloylamino group and a surface-treated glass cloth surface-treated with the treating liquid. Background Art
[0002] Now, along with the high performance and high speed communication of information terminals such as smart phones, in the printed wiring board used, while high density and extremely thin, low dielectric and low dielectric loss tangent are developed significantly. As the insulating material of the printed wiring board, the prepreg laminated and heated and pressurized cured by making glass cloth impregnated with thermosetting resins such as epoxy resin (hereinafter referred to as "matrix resin") is widely used. The demand of such laminated board is further improving, and it is hoped that the productivity will be improved.
[0003] However, since glass cloth, which is a substrate material, has low strength, there is a limit to the coating speed of the resin on the glass cloth, and it is difficult to improve productivity.
[0004] Generally, as a method for improving the strength of glass cloth, a method of reacting a silane coupling agent with a silanol group of the glass cloth is adopted. So far, treatments with various silane coupling agents have been studied, but the strength of these treatments is not sufficient.
[0005] In addition, generally, when a silane coupling agent is used to improve the strength of glass cloth, it is used in the form of an aqueous solution in which about 1% by mass of the silane coupling agent is dissolved in water. As a silane coupling agent used in a glass cloth treatment solution, 3-methacryloxypropyltrimethoxysilane reported in Patent Document 1 is a representative one.
[0006] However, the glass cloth treating liquid using 3-methacryloxypropyltrimethoxysilane has a problem of low storage stability and short pot life because the condensation reaction of the silanol group generated by hydrolysis proceeds slowly.
[0007] Patent Document 2 reports a silane coupling agent containing a methacrylamide group as a silane coupling agent for treating glass cloth. It is reported that a laminate using glass fibers treated with the silane coupling agent has excellent properties such as heat resistance. The silane coupling agent is a mixture of a compound obtained by reacting 1 equivalent of methacryloyl chloride with 3-aminopropyltriethoxysilane and a compound obtained by reacting 2 equivalents of 3-aminopropyltriethoxysilane. The dimethylacrylamide compound obtained by reacting 2 equivalents has a problem in that the storage stability of the aqueous solution is low due to its high hydrophobicity.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 2020 / 194772
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 5-25219 Summary of the invention
[0012] Problems to be solved by the invention
[0013] The present invention has been made in view of the above problems, and an object of the present invention is to provide a glass cloth treating solution containing a methacrylamide-containing organosilicon compound and having excellent storage stability, and a surface-treated glass cloth having excellent strength which has been surface-treated with the glass cloth treating solution.
[0014] Means for solving problems
[0015] The present inventors have conducted intensive studies to solve the above problems and have found that an aqueous solution containing an organosilicon compound containing a methacrylamido group and an organooxy group at a specific concentration and substantially containing no organosilicon compound containing a dimethacrylamido group has excellent stability, thereby completing the present invention.
[0016] That is, the present invention provides:
[0017] 1. A glass cloth treating liquid, comprising 0.05 to 2.0 mass % of an organosilicon compound containing a methacrylamide group represented by the following formula (1) dissolved in water, wherein the content of the organosilicon compound containing a dimethacrylamide group represented by the following formula (2) is less than 1 mass part relative to 100 mass parts of the organosilicon compound containing a methacrylamide group represented by the following formula (1),
[0018] [Chemistry 1]
[0019]
[0020] (Where R 1 Each independently represents an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 20 carbon atoms, Me represents a methyl group, m1 and m2 represent integers of 1 to 3, and n1 and n2 represent integers of 1 to 12.
[0021] 2. The glass cloth treating solution according to 1, wherein in the formula (1) and the formula (2), R 1 is methyl, n1 and n2 are 3;
[0022] 3. The glass cloth treating liquid according to 1 or 2, wherein the water is water adjusted to be acidic;
[0023] 4. A surface-treated glass cloth, wherein the surface of the glass cloth is treated with the glass cloth treating solution according to 1 or 2;
[0024] 5. The surface-treated glass cloth according to 4, wherein 0.05 to 0.5 mass % of the organosilicon compound containing a methacrylamide group represented by the formula (1) is attached to the glass cloth;
[0025] 6. The surface-treated glass cloth according to 4, wherein the unit cloth mass (g / mm 2 ) has a tensile strength of 2.1 times greater than that before surface treatment;
[0026] 7. A prepreg comprising the surface-treated glass cloth according to 4, and a matrix resin impregnated with the surface-treated glass cloth;
[0027] 8. A printed wiring board using the prepreg according to 7.
[0028] Effects of the Invention
[0029] The glass cloth treating solution of the present invention has excellent storage stability. In addition, the glass cloth treated with the glass cloth treating solution of the present invention has excellent strength and can be suitably used in printed wiring boards, etc., and can improve the productivity and reliability of the board during board manufacturing. DETAILED DESCRIPTION
[0030] The present invention is described in detail below.
[0031] [Glass cloth treatment liquid]
[0032] The glass cloth treating liquid of the present invention (hereinafter sometimes referred to as "treating liquid") is an aqueous solution containing a methacryloylamino-containing organosilicon compound represented by the following formula (1) (hereinafter referred to as compound (1)) and substantially free of a dimethacryloylamino-containing organosilicon compound represented by the following formula (2) (hereinafter referred to as compound (2)).
[0033] In the present invention, “substantially free” means that the content of the compound (2) is less than 1 part by mass, preferably less than 0.5 part by mass, and more preferably 0 part by mass, based on 100 parts by mass of the compound (1).
[0034] [Chemistry 2]
[0035]
[0036] In the formula, R 1Each independently represents an alkyl group having 1 to 10 carbon atoms, preferably 1 to 8 carbon atoms, and more preferably 1 to 6 carbon atoms, or an aryl group having 6 to 20 carbon atoms, preferably 6 to 10 carbon atoms, and more preferably 6 to 8 carbon atoms; Me represents a methyl group; m1 and m2 represent an integer of 1 to 3; and n1 and n2 represent an integer of 1 to 12.
[0037] As R 1 The alkyl group may be a linear, branched or cyclic group having 1 to 10 carbon atoms. Specific examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl and cyclooctyl groups.
[0038] Specific examples of the aryl group having 6 to 20 carbon atoms include phenyl, α-naphthyl, β-naphthyl and the like.
[0039] Among these, R 1 , preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and still more preferably a methyl group.
[0040] m1 and m2 represent integers of 1 to 3, preferably 2 or 3, and n1 and n2 represent integers of 1 to 12, preferably integers of 1 to 8, more preferably integers of 1 to 4, and further preferably 3, from the viewpoint of raw material procurement.
[0041] Therefore, as compound (1), further preferred is one in which R 1 The compound wherein R 1 is a methyl group, and n1 is 3. In addition, correspondingly, as for compound (2), there can be mentioned compounds in which R 1 is methyl or ethyl, n2 is 3, especially wherein R 1 The compound wherein n2 is 3 and the methyl group is methyl.
[0042] Specific examples of the compound (1) include methacrylamidomethyltrimethoxysilane, methacrylamidomethylmethyldimethoxysilane, methacrylamidomethyltriethoxysilane, methacrylamidomethylmethyldiethoxysilane, 3-methacrylamidopropyltrimethoxysilane, 3-methacrylamidopropylmethyldimethoxysilane, 3-methacrylamidopropyltriethoxysilane, 3-methacrylamidopropylmethyldiethoxysilane, 4-methacrylamidobutyltrimethoxysilane, 4-methacrylamidobutylmethyldimethoxysilane, 4-methacrylamidopropyl ... Amidobutyltriethoxysilane, 4-methacrylamidobutylmethyldiethoxysilane, 8-methacrylamidooctyltrimethoxysilane, 8-methacrylamidooctylmethyldimethoxysilane, 8-methacrylamidooctyltriethoxysilane, 8-methacrylamidooctylmethyldiethoxysilane, 12-methacrylamidododecyltrimethoxysilane, 12-methacrylamidododecylmethyldimethoxysilane, 12-methacrylamidododecyltriethoxysilane, 12-methacrylamidododecylmethyldiethoxysilane, etc., but are not limited to these. These can be used alone or in combination of two or more.
[0043] Among these, compounds represented by the following formula are preferred, and compounds (1-1) and (1-3) are particularly preferred from the viewpoint of production and aqueous solution preparation. In the following formula, Me represents a methyl group, and Et represents an ethyl group.
[0044] [Chemistry 3]
[0045]
[0046] The method for producing compound (1) is not particularly limited, and a conventionally known production method can be used. For example, it can be obtained by reacting a methacrylate such as methyl methacrylate with an aminoalkylalkoxysilane such as 3-aminopropyltrimethoxysilane at a temperature of about 100 to 200° C. in the presence of a polymerization inhibitor and an amidation catalyst according to the method described in Japanese Patent No. 3561501.
[0047] The glass cloth treating liquid of the present invention does not substantially contain compound (2). Specific examples of compound (2) include N,N-dimethylacrylamidomethyltrimethoxysilane, N,N-dimethylacrylamidomethylmethyldimethoxysilane, N,N-dimethylacrylamidomethyltriethoxysilane, N,N-dimethylacrylamidomethylmethyldiethoxysilane, 3-(N,N-dimethylacrylamido)propyltrimethoxysilane, 3-(N,N-dimethylacrylamido)propylmethyldimethoxysilane, 3-(N,N-dimethylacrylamido)propyltriethoxysilane, 3-(N,N-dimethylacrylamido)propylmethyldiethoxysilane, 4-(N,N-dimethylacrylamido)butyltrimethoxysilane, and 4-(N,N-dimethylacrylamido)butylmethyldimethoxysilane. , 4-(N,N-dimethylacrylamido)butyltriethoxysilane, 4-(N,N-dimethylacrylamido)butylmethyldiethoxysilane, 8-(N,N-dimethylacrylamido)octyltrimethoxysilane, 8-(N,N-dimethylacrylamido)octylmethyldimethoxysilane, 8-(N,N-dimethylacrylamido)octyltriethoxysilane, 8-(N,N-dimethylacrylamido)octylmethyldiethoxysilane, 12-(N,N-dimethylacrylamido)dodecyltrimethoxysilane, 12-(N,N-dimethylacrylamido)dodecylmethyldimethoxysilane, 12-(N,N-dimethylacrylamido)dodecyltriethoxysilane, 12-(N,N-dimethylacrylamido)dodecylmethyldiethoxysilane, etc., but are not limited to these. When these compounds are contained, they may be contained alone or in combination of two or more.
[0048] Among these, a representative compound of the compound (2) is represented by the following formula, particularly the compound (2-1) or the compound (2-3). In the following formula, Me represents a methyl group, and Et represents an ethyl group.
[0049] [Chemistry 4]
[0050]
[0051] In the glass cloth treatment liquid of the present invention, compound (1) is dissolved in water. The content of compound (1) in the glass cloth treatment liquid is 0.05 to 2.0% by mass, preferably 0.05 to 1.5% by mass, and more preferably 0.1 to 1% by mass. When the content is less than 0.05% by mass, the amount of silane coupling agent relative to the silanol group of the glass cloth is insufficient, and the strength of the glass cloth cannot be fully improved. When the content exceeds 2.0% by mass, the storage stability of the treatment liquid is impaired, and the glass cloth becomes rigid, thereby reducing the productivity of the substrate material.
[0052] The glass cloth treating liquid of the present invention can be prepared by mixing compound (1) and water to dissolve compound (1) in water. In this case, compound (1) may be added to water or water may be added to compound (1), but the method of adding compound (1) to water is preferred, and the method of dropping compound (1) into water is more preferred.
[0053] The addition temperature is preferably 10 to 50°C, more preferably 15 to 40°C.
[0054] The glass cloth treating liquid of the present invention may contain an organic solvent in addition to the compound (1) and water within a range not impairing the effects of the present invention.
[0055] The organic solvent is not particularly limited, but preferably is an organic solvent with excellent compatibility with water, for example, alcohols such as methanol, ethanol, isopropanol; ethers such as diethyl ether, tetrahydrofuran, 1,4-dioxane; esters such as ethyl acetate; ketones such as acetone, methyl ethyl ketone, etc., and one kind may be used alone or two or more kinds may be used in combination.
[0056] In the case where the above-mentioned organic solvent is not used, the glass cloth treatment liquid of the present invention preferably uses water adjusted to acidity from the viewpoint of stability. As the acid used for adjusting to acidity, organic acids such as formic acid, acetic acid, and citric acid, inorganic acids such as hydrochloric acid, etc. can be listed. When an acid is used, the amount added is preferably 0.001 to 0.5% by mass of the total treatment liquid, and more preferably 0.01 to 0.1% by mass. In addition, when an acid is used, water adjusted to acidity by mixing the acid with water in advance can be used, and an acid can also be added to an aqueous solution containing compound (1) to adjust to acidity.
[0057] The glass cloth treating liquid of the present invention may contain an alkoxy group-containing organosilicon compound, a silazane compound or the like other than the compound (1) to improve adhesion and adhesiveness to the glass cloth as required, within a range not impairing the effects of the present invention.
[0058] In addition, other additives can be added to the glass cloth treatment liquid of the present invention as required within the range that does not impair the effects of the present invention. Specific examples of other additives include water-soluble resins, curing catalysts, physical property modifiers for adjusting the tensile properties of the generated cured film, storage stability improvers, surfactants, metal deactivators, ozone degradation inhibitors, lubricants, pigments, etc.
[0059] [Surface treated glass cloth]
[0060] The surface treated glass cloth of the present invention is a glass cloth whose surface is treated with the above treatment liquid. The surface treated glass cloth of the present invention can be obtained by applying the glass cloth treatment liquid of the present invention to the surface of the glass cloth and heating and drying it as needed.
[0061] [1] Glass cloth
[0062] The glass fibers constituting the glass cloth used as the substrate are not particularly limited, and glass cloth of a conventionally known glass composition can be used. Specific examples thereof include E glass, S glass, C glass, D glass, T glass, NE glass, Q glass (quartz glass), etc., which can be appropriately selected according to the intended use.
[0063] The form of the glass yarn is not particularly limited, and examples thereof include filaments, bundles of 20 to 400 filaments, and yarns obtained by twisting bundles.
[0064] The thickness of the glass cloth is not particularly limited, but is preferably 5 to 300 μm, more preferably 20 to 200 μm, and still more preferably 30 to 150 μm. The mass per unit area is not particularly limited, but is preferably 10 to 200 g / m 2 , more preferably 20 to 150 g / m 2 .
[0065] The weaving structure of the glass cloth is not particularly limited, and examples thereof include plain weave, twill weave, twill weave, satin weave, etc. These are appropriately selected according to the intended use, and the weaving density is also appropriately selected within a conventionally known range.
[0066] [2] Method for manufacturing glass cloth
[0067] The method for producing the glass cloth used as the substrate is not particularly limited as long as it includes a step of weaving glass yarns, and examples thereof include a method including the following steps.
[0068] (1) Weaving process of weaving glass yarn to obtain glass cloth
[0069] (2) Opening process of opening glass fibers of glass cloth
[0070] (3) Thermal cleaning process to remove the sizing agent attached to the glass fibers of the glass cloth
[0071] (1) Weaving process
[0072] The weaving process is a process of weaving glass yarns to obtain glass cloth. The weaving method is not particularly limited, and examples thereof include weaving methods using air jet looms, water jet looms, rapier looms, shuttle looms, etc. When weaving using air jet looms, etc., PVA or starch can be attached as a secondary sizing agent in order to obtain further lubricity.
[0073] (2) Fiber opening process
[0074] The fiber opening step is a step of opening the glass fibers of the glass cloth. The fiber opening method is not particularly limited, and examples thereof include fiber opening methods such as water spraying (high-pressure water fiber opening), an oscillating washing machine, ultrasonic water, and a cloth mangling machine.
[0075] (3) Thermal cleaning process
[0076] The heat cleaning step is a step of removing the sizing agent remaining on the surface of the woven glass cloth. The residual sizing agent deteriorates the dielectric properties when the surface-treated glass cloth is used as a substrate material, and the surface treatment of the glass cloth becomes insufficient, resulting in poor adhesion to the resin, which is not preferred.
[0077] As a method of thermal cleaning, there are methods using a fluidized or intermittent heating furnace. In the fluidized method, the sizing agent is burned off at high temperature all at once, which has the problem of reduced strength of the glass cloth and residual embers of the sizing agent. Therefore, the intermittent method is generally used to slowly burn and remove organic matter at 300 to 400°C.
[0078] [3] Surface treatment method of glass cloth
[0079] The surface treatment method of the glass cloth using the glass cloth treatment liquid of the present invention is not particularly limited, and can be carried out, for example, by a method including the following steps.
[0080] (11) A treatment liquid contacting step of bringing the glass cloth treatment liquid of the present invention into contact with the surface of the glass cloth
[0081] (12) A reaction step of reacting the silanol groups on the surface of the glass cloth with the organic oxygen groups in the compound (1) contained in the glass cloth treating liquid of the present invention.
[0082] (11) Treatment liquid contact step
[0083] The treatment liquid contact step is a step of contacting the glass cloth treatment liquid of the present invention with the surface of the glass cloth. In the treatment liquid contact step, the contact method is not particularly limited and can be appropriately selected from known methods, such as a method of impregnating the glass cloth with the glass cloth treatment liquid of the present invention, a method of using a roller coating, etc.
[0084] (12) Reaction process
[0085] The reaction step is a step of reacting the silanol groups on the surface of the glass cloth with the organic radicals in the compound (1) contained in the glass cloth treatment solution of the present invention. In the reaction step, the reaction conditions are not particularly limited and can be appropriately adjusted according to the heat resistance of the glass filaments, the amount of the glass cloth treatment solution used, etc. The reaction temperature is preferably 70 to 200° C., more preferably 90 to 150° C. The reaction time is preferably 30 seconds to 30 minutes, more preferably 1 to 20 minutes. Under such conditions, water can be evaporated to react with the compound (1) and the silanol groups on the surface of the glass cloth.
[0086] The heating method is not particularly limited and can be appropriately selected from known methods. Examples of the heating method include methods using hot air, infrared rays, and heat rolls.
[0087] In the surface-treated glass cloth of the present invention, the amount of compound (1) attached to the base glass cloth is not particularly limited, but is preferably 0.05 to 0.5% by mass, more preferably 0.05 to 0.2% by mass, from the viewpoint of processability and strength. The amount of compound (1) attached can be measured by the heat loss method described in JIS R3420:2013.
[0088] The unit cloth mass (g / mm 2 ) is preferably 2.1 times or more, more preferably 2.2 times or more, compared to that before the surface treatment. Such a surface treated glass cloth has excellent processability when it is prepreg-formed. It should be noted that, as described later, the measurement of tensile strength can be carried out according to "7.4 Tensile Strength" of JIS R3420:2013 "General Test Methods for Glass Fibers".
[0089] [Prepreg]
[0090] The prepreg of the present invention comprises the surface-treated glass cloth and a matrix resin in which the surface-treated glass cloth is impregnated.
[0091] The surface-treated glass cloth of the present invention can be mixed with a matrix resin to form a prepreg. The prepreg obtained by using the surface-treated glass cloth of the present invention has excellent strength and can be suitably used in, for example, a printed wiring board.
[0092] The method for producing the prepreg of the present invention is not particularly limited, and a general method for producing a substrate, film, or prepreg containing glass cloth can be applied. For example, a method of impregnating a surface-treated glass cloth with a molten matrix resin or a solution containing a matrix resin can be adopted.
[0093] The matrix resin used for the prepreg of the present invention is not particularly limited and can be appropriately selected from conventionally known matrix resins, such as thermosetting silicone resins, polyimide resins, maleimide resins, epoxy resins, cyanate resins, (meth)acrylic resins, etc.
[0094] The thickness of the prepreg of the present invention is not particularly limited, but is preferably 10 to 400 μm, more preferably 30 to 300 μm, and further preferably 40 to 200 μm. Within this range, for example, when the prepreg of the present invention is used for a printed wiring board, a substrate such as a copper-clad laminate can be well prepared.
[0095] The prepreg of the present invention may be semi-cured (B-staged) by heating in advance. The method of B-staged is not particularly limited, and for example, the matrix resin may be dissolved in a solvent, impregnated into glass cloth, dried, and then heated at 80 to 200° C. for 1 to 30 minutes to achieve B-staged.
[0096] [Printed wiring board]
[0097] The printed wiring board of the present invention is obtained using a prepreg containing the surface-treated glass cloth of the present invention. There is no particular limitation on the method for manufacturing the printed wiring board of the present invention, and a general method for manufacturing a printed substrate can be applied. As a specific example, for example, a method for manufacturing a substrate as a copper-clad laminate by overlapping the prepreg of the present invention with copper foil, applying pressure, and heat-curing it can be cited. There is no particular limitation on the method for manufacturing a copper-clad laminate, and for example, it can be manufactured by using 1 to 20 sheets, preferably 2 to 10 sheets, of the above-mentioned prepreg, arranging copper foil on one or both sides thereof, applying pressure, and heat-curing it.
[0098] The thickness of the copper foil is not particularly limited, preferably 3 to 70 μm, more preferably 10 to 50 μm, and further preferably 15 to 40 μm. If it is within this range, a multi-layer copper-clad laminate with high reliability can be formed. There is no particular restriction on the molding conditions of the copper-clad laminate. For example, a multi-stage press, a multi-stage vacuum press, continuous molding, an autoclave molding machine, etc. can be used to mold at a temperature of 100 to 400°C, a pressure of 1 to 100 MPa, and a heating time of 0.1 to 4 hours. In addition, the prepreg, copper foil, and inner layer wiring board of the present invention can also be combined to form a copper-clad laminate.
[0099] There is no particular limitation on the method of circuit processing, and examples thereof include methods of circuit formation processing by opening, metal plating, etching of metal foil, etc. In addition, a printed wiring board can be manufactured by a build-up method in which a composition containing a matrix resin or the prepreg of the present invention and copper foil are sequentially stacked.
[0100] Example
[0101] The present invention is described in more detail below with reference to Synthesis Examples, Examples and Comparative Examples, but the present invention is not limited to these Examples. In the following formulae, Me represents a methyl group, and Et represents an ethyl group.
[0102] [1] Synthesis of organosilicon compounds
[0103] [Synthesis example 1]
[0104] With reference to Japanese Patent No. 3561501, a methacrylamido group-containing organosilicon compound (1-1) represented by the following formula was obtained.
[0105] [Chemistry 5]
[0106]
[0107] [Synthesis example 2]
[0108] With reference to Japanese Patent No. 3561501, a methacrylamido group-containing organosilicon compound (1-3) represented by the following formula was obtained.
[0109] [Chemistry 6]
[0110]
[0111] [Comparative Synthesis Example 1]
[0112] With reference to Japanese Patent Application Laid-Open No. 5-25219, a mixture (3-1) of a methacrylamide-containing organosilicon compound and a dimethacrylamido-containing organosilicon compound represented by the following formula was obtained.
[0113] [Chemistry 7]
[0114]
[0115] [2] Manufacture of glass cloth treatment liquid
[0116] [Examples 1-1 to 1-3, Comparative Examples 1-1 to 1-6]
[0117] According to the blending ratio shown in Table 1, the compounds obtained in Synthesis Examples 1 and 2, the mixture obtained in Comparative Synthesis Example 1 or other comparative compounds were dropped into 0.05 mass % acetic acid water at 25° C. to prepare a glass cloth treatment liquid.
[0118] The following evaluations were performed on the obtained glass cloth treatment liquid. The results are collectively shown in Table 1.
[0119] [3] Evaluation of the stability of the treatment fluid
[0120] The appearance of the obtained aqueous solution after being left to stand in an environment of 25° C. for 1 day, 7 days, and 14 days was visually observed and evaluated according to the following criteria.
[0121] ○: Completely dissolved to form a uniform aqueous solution.
[0122] ×: Insoluble matter precipitated.
[0123] [4]Manufacture of surface treated glass cloth
[0124] [Examples 2-1 to 2-3, Comparative Examples 2-1 to 2-6]
[0125] The sizing agent was removed by heating at 400°C for 72 hours, and the obtained E glass cloth (thickness: 95 μm, mass per unit area: 107 g / m 2 ) was immersed in the glass cloth treating solution obtained in Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-6, taken out, and then heated and dried at 110° C. for 10 minutes to obtain a surface treated glass cloth.
[0126] [5] Evaluation of tensile strength of surface treated glass cloth
[0127] The unit cloth weight (g / mm2) of the surface-treated glass cloth obtained above was measured using Autograph and AGS-X manufactured by Shimadzu Corporation in accordance with JIS R3420:2013 (general test methods for glass fibers). 2 The tensile strength of the glass cloth was measured and the ratio of the tensile strength to the glass cloth before treatment was calculated. The results are shown in Table 2.
[0128] [6] Determination of the amount of surface treatment agent adhered
[0129] For the surface treated glass cloth produced in the same manner as the surface treated glass cloth used in the tensile strength test, the adhesion amount (mass %) of the compounds obtained in Synthesis Examples 1 and 2 and the mixture or comparative compound (surface treatment agent (silane coupling agent)) obtained in Comparative Synthesis Example 1 was measured according to the determination method of the loss on heat of JIS R3420. The results are shown in Table 2.
[0130] [Table 1]
[0131]
[0132] ·KBM-503 (3-methacryloxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0133] ·KBM-903 (3-aminopropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0134] [Table 2]
[0135]
[0136] As shown in Tables 1 and 2, the glass cloth treating solutions of Examples 1-1 to 1-3 were excellent in storage stability, and the glass cloth surface-treated with the glass cloth treating solutions of Examples 1-1 to 1-3 was excellent in tensile strength.
[0137] On the other hand, in Comparative Example 1-1 including the organosilicon compound containing a dimethylacrylamide group, the storage stability of the glass cloth treatment liquid was significantly poor.
[0138] In addition, when the proportion of the organosilicon compound containing methacryloylamino group in the glass cloth treatment liquid is insufficient, the tensile strength of the glass cloth is poor (Comparative Example 2-2), and when the proportion of the organosilicon compound containing methacryloylamino group is too high, the storage stability of the treatment liquid is significantly deteriorated (Comparative Example 1-3).
[0139] The tensile strength of the glass cloth treated with the glass cloth treating solution containing 3-methacryloxypropyltrimethoxysilane was poor (Comparative Examples 2-4). In order to improve the tensile strength, when the amount of 3-methacryloxypropyltrimethoxysilane added was increased, the storage stability of the treating solution was significantly deteriorated (Comparative Examples 1-5).
[0140] The tensile strength of the glass cloth treated with the glass cloth treating solution containing 3-aminopropyltrimethoxysilane was poor (Comparative Example 2-6).
Claims
1. A glass cloth treating liquid, comprising 0.05 to 2.0% by mass of a methacrylamide-containing organosilicon compound represented by the following formula (1) dissolved in water, wherein: The content of the dimethacryloylamino group-containing organosilicon compound represented by the following formula (2) is less than 1 part by mass based on 100 parts by mass of the methacrylamido group-containing organosilicon compound represented by the following formula (1). [Chemistry 1] In the formula, R 1 Each independently represents an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 20 carbon atoms, Me represents a methyl group, m1 and m2 represent integers of 1 to 3, and n1 and n2 represent integers of 1 to 12.
2. The glass cloth treating solution according to claim 1, wherein: In the formula (1) and the formula (2), R 1 is a methyl group, and n1 and n2 are 3.
3. The glass cloth treating liquid according to claim 1 or 2, wherein: The water is water adjusted to be acidic.
4. Surface treated glass cloth, wherein: The surface of the glass cloth is treated with the glass cloth treating liquid according to claim 1 or 2.
5. The surface-treated glass cloth according to claim 4, wherein: 0.05 to 0.5 mass % of the methacrylamide-containing organosilicon compound represented by the formula (1) adheres to the glass cloth.
6. The surface-treated glass cloth according to claim 4, wherein: Unit cloth mass (g / mm 2 ) has a tensile strength 2.1 times greater than that before surface treatment.
7. A prepreg comprising the surface-treated glass cloth according to claim 4, and a matrix resin impregnating the surface-treated glass cloth.
8. A printed wiring board using the prepreg according to claim 7.
Citation Information
Patent Citations
Output buffer reducing earth rebound noise significantly
JP1989060107A
Silane coupling agent and glass fiber product for laminate
JP1993025219A
Surface-treated glass cloth, prepreg, and printed wiring board
WO2020194772A1